Recalcitrant chronic rhinosinusitis in the setting of fucosidosis, a rare lysosomal storage disorder. (December 2017) - Peng, Tiffany; Modi, Vikash K.; Pearlman, Aaron N.
Abstract: Fucosidosis is an autosomal recessive lysosomal storage disorder caused by the deficiency of alpha-L-fucosidase. We present the case of an affected female in the second decade of life with chronic rhinosinusitis (CRS) including recalcitrant polypoid inflammation, which has not been previously reported in the literature. With the advancement of life-prolonging measures, children with lysosomal storage disorders may suffer increasingly from CRS due to the lymphohistiocytic and macrophage infiltrate of the paranasal sinus mucosa that resembles severe polypoid inflammation.